F Factors Affecting Non Compliance with Hypertension Patients' Drug Use in the Region of Cempaka Putih Puskesmas, Banjarmasin (INTEGRATION PROCEEDING, 2023)
Hypertension is a health problem that is quite dangerous throughout the world because hypertension is a major risk factor that leads to heart disease and stroke. This disease is one of the leading causes of death in the world. Non-compliance with hypertension treatment will cause various complications of organ damage, such as causing heart disease, kidney failure or stroke which can lead to death To determine the factors that influence the non-compliance of drug use in hypertension patients in the Cempaka Putih Health Center Banjarmasin Using observational analytic with a cross-sectional approach Sampling with purposive sampling technique The sample is outpatient hypertension at Cempaka Putih Health Center Banjarmasin totaling 43 people, analyzed using descriptive analytical method and the Chi-Square test with 95% confidence level.Gender with P-Value = 0.059 and OR = 0.200, Family income with P-Value = 0.427 and OR = 1.950, and distance to health services has a significant effect with P-Value = 0.000 and OR = 1.778, while the other 2 factors, namely gender and family income, did not have a significant influence on non-adherence to the use of hypertension patients in the Cempaka Putih Health Center area, Banjarmasin.Conclusion: There are factors that influence non-compliance with the use of hypertension drugs in the Cempaka Putih Health Center Banjarmasin area, namely there is an influence between distance to health services and non-compliance with the use of hypertension drugs.Keywords: Factors, Non-compliance, Drug Use in Hypertensive Patients